Effectiveness of Tai Chi intervention for Major Depressive Disorder: a systematic review and meta-analysis - Chen, Limei; Cheng, Yu; Huang , Ruohui; Ni, Zixiang; Zhou, Chenwei (The Journal of the International Society of Chinese Health Practices, 2025)
See PDF for details